EMOTIONALLY UNSTABLE PEROSNALITY DISORDER CAN CREATE SUICIDAL THROUGH IN A PERSON ‘S MIND - HARISHCHANDRA RAM (International Journal of Multidisciplinary Research and Studies, 2021)
Emotionally unstable personality disorder (EUPD), also known as borderline personality disorder, is a mental health condition that can affect a person's emotions, behavior, and relationships with others. People with EUPD may experience intense and unstable emotions, have difficulty regulating their emotions, and have impulsive and self-destructive behaviors.One of the potential risks associated with EUPD is an increased risk of suicidal thoughts and behaviors. This may be due to the intense emotional pain and distress that people with EUPD can experience, as well as the impulsive and self-destructive behaviors that can be associated with the disorder.It's important to note that not all people with EUPD will experience suicidal thoughts or behaviors, and that there are effective treatments available for EUPD that can help manage symptoms and reduce the risk of self-harm. If you or someone you know is experiencing suicidal thoughts or behaviors, it's important to seek help from a mental health professional or a crisis hotline immediately.